A turn-on fluorescent probe with high selectivity for Hg2+ and its applications in living cells. Issue 33 (1st August 2022) - Li, Bin; Tian, Fuli; Hua, Yupeng
Abstract : A novel colorimetric fluorescent probe with low detection limits has been designed and synthesized, which shows an unique response for Hg 2+ in living cells. Abstract : A novel fluorescent probe L with a rhodamine B lactam structure modified with 3-methyl-2-thiophenecarboxaldehyde has been prepared based on the thiophilicity of Hg 2+ . The probe L exhibits a unique response with an "off–on-type" mode towards Hg 2+ among other biologically relevant metal cations. The limit of detection (LOD) for probe L is 1.5 ppb. In addition, in the presence of Hg 2+, the probe L shows a colorimetric response from colorless to pink. The recognition behavior of probe L towards Hg 2+ has been investigated by 1 H NMR titration experiments, Job's plot, and MS and IR analyses. As a result, the ligation between the probe and Hg 2+ leads to the scission of the spirolactam bond of free L and the restoration of its conjugated structure, which can give rise to the fluorescence enhancement of the probe L . Besides, it also can be used as a sensitivity probe in living cells for Hg 2+ sensing, which can meet various needs in genetic and environmental samples.